Optimizing Repair and Maintenance of Waste-Processing Machinery for Sustainable Environmental Management in Pariaman City - Budi Riyanto; I Kadek Laju; Riki Wanda Putra; Arya Widiatmaja; Hasri Devin; Akbar Alim (Bulletin of Pedagogical Research, 2025)
This study addresses persistent waste-management challenges in coastal urban areas by optimizing the performance of waste-processing equipment at the Reduce-Reuse-Recycle (TPS3R) facility in Pariaman City. It was conducted through a Reliability-Centered Maintenance (RCM)–based repair and preventive maintenance program. The intervention combined field observation, identification of critical components, operator technical training, and the implementation of a structured maintenance schedule adapted to local operational conditions. Implementation involved collaboration among TPS3R management, local community members, and technical staff from Politeknik Pelayaran Sumatera Barat. Data were collected through direct observation, semi-structured interviews, and documentation of maintenance activities. Post-intervention evaluation demonstrated substantive gains in machine processing efficiency, up to an 80% improvement relative to baseline and a marked reduction in breakdown frequency. Operators showed measurable increases in technical competence and consistent adherence to Standard Operating Procedures (SOPs) for safe and effective machine operation. The findings underscore the value of vocational higher-education–community partnerships for technology adaptation, capacity building, and fostering a maintenance culture that supports sustainable urban waste systems. The program represents a scalable, replicable model for similar coastal contexts and contributes to Sustainable Development Goals 11 (Sustainable Cities and Communities) and 12 (Responsible Consumption and Production).